Mini-puberty and true puberty: Differences in testicular function - Rey, Rodolfo Alberto (2014)
The ontogeny of the hypothalamic-pituitary-gonadal axis is particularly characterised by incomplete functional maturation in utero and during early postnatal life, followed by functional regression and partial quiescence during childhood, and subsequently by final complete maturation during puberty. This review addresses the distinctive features of testis developmental physiology – especially in the seminiferous tubule compartment – which explain the differences observed in testicular function and its disorders between the early postnatal activation period – which many authors call “mini-puberty” – and canonical puberty.